Towards a design-based approach to accounting research - Christian Leuz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
Armstrong et al. (2022) review the empirical methods used in the accounting literature to draw causal inferences. They document a growing number of studies using quasi-experimental methods and provide a critical perspective on this trend as well as the use of these methods in the accounting literature. In this discussion, I complement their review by broadening the perspective. I argue for a design-based approach to accounting research that shifts attention from methods to the entire research design. I also discuss why studies that aim to draw causal inferences are important, how these studies fit into the scientific process, and why assessing the strength of the research design is important when evaluating studies and aggregating research findings.
urn:nbn:de:hebis:30:3-691204
Keywords: C4; D8; M4; 330; Endogeneity; Causal inferences; Research design; Empirical methods; Natural experiments; Accounting research